Molecular typing of Indian Salmonella isolates from poultry samples - SIDDIQUE, R A; SAXENA, M; LAKHCHAURA, B D (The Indian Journal of Animal Sciences, 2011)
Genus Salmonella consists of an important zoonotic, ubiquitous, organisms causing disease in human as well as animals. In the present study molecular typing of Indian Salmonella isolates, 300 poultry samples (fecal, meat and egg) were screened for Salmonella. Rapidly detected by targeting invA gene, giving PCR product of 284 bp size. Positive samples of Salmonella were serotyped. Five RAPD primers were used to generate randomly amplified polymorphic DNA fragments. RAPD of 24 Salmonella isolates by all 5 primers generated 122 loci. Out of which, 18 were unique and 104 loci were polymorphic. The size of these fragments ranged from 200 bp to 3.0 Kbp. Dendrogram of RAPD for 24 Salmonella isolates revealed similarly between 14.3 to 50%, It is concluded that RAPD technique can be used to demonstrate differences among same serovars of Salmonella.